Development of Malaysia’s Traditional Instruments Mobile Application with Marker-less Augmented Reality - Nur Hannani Afrina Mohd Hasram; Rahayu A Hamid (Applied Information Technology And Computer Science, 2024)
Traditional musical instruments have been around in Malaysia for hundreds of years. It is used in traditional and classical musical instruments. However, in this modern era, it is rare to see these instruments in real life. Mobile application that displays these instruments are scarce on Google Play and the existing applications are yet to be implemented with marker-less augmented Reality (AR) technology. Therefore, this project is proposed to develop a mobile application using marker-less AR technology namely "Malaysia’s Traditional Instruments" that allows users in the range of age of 7 years old and above to learn and play the instruments. The project is developed using the Multimedia Mobile Content Development (MMCD) approach. The application will allow users to learn without the need to visit museums and attend traditional performances. This application is tested by 30 users in the range of 7 years old and above and has passed the user acceptance and functional test.